PENGARUH KARAKTERISTIK KELUARGA DAN STATUS GIZI ANAK DENGAN PERKEMBANGAN KOGNITIF ANAK USIA PRASEKOLAH DI KOTA BOGOR - Dwi Anggraeni Puspitasari; Lilik Kustiyah; Cesilia Meti Dwiriani; Yekti Widodo (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2021)
ABSTRACT The incidence of stunting and delays in cognitive abilities is a problem that still occurs in Indonesia. This study aims to analyze the effect of family characteristics and subject characteristics on cognitive abilities in preschool children in the city of Bogor. This study uses a case-control design on some of the data from the Child Development Cohort (TKA) study located in the city of Bogor. The case group is preschool children with delayed cognitive development and the control group is preschool children with normal cognitive development. The number of subjects in this study was 84 children, consisting of 42 children in the case group and 42 children in the control group. The variables analyzed included family characteristics (parental education, parental occupation, and family size), subject characteristics (gender, anthropometry at birth, nutritional status at birth), health status, and the parenting environment, and children's cognitive development. The results of the analysis show that the increase in height of children 0-4 years has an effect on the cognitive development of preschool children. Children with height gain that is not in accordance with WHO standards are at risk of 4.1 times experiencing delayed cognitive development. In an effort to increase the growth and cognitive development of children, access to education and the provision of a good nurturing environment must be increased. Fulfilling the nutritional needs of preschool children that are appropriate so that children's height growth is optimal and providing good psychosocial parenting can optimize their cognitive development. In addition, the provision of stimulation according to the child's age is needed to support more optimal growth and development of children. ABSTRAK Kejadian stunting dan keterlambatan kemampuan kognitif merupakan masalah yang masih terjadi di Indonesia. Penelitian ini bertujuan untuk menganalisis pengaruh karakteristik keluarga dan karakteristik subjek terhadap kemampuan kognitif pada anak usia prasekolah di Kota Bogor. Penelitian ini menggunakan desain kasus kontrol pada sebagian data studi Kohor Tumbuh Kembang Anak (TKA) yang berlokasi di Kota Bogor. Kelompok kasus adalah anak prasekolah yang mengalami gangguan perkembangan kognitif terlambat dan kelompok kontrol yakni anak prasekolah dengan perkembangan kognitif normal. Jumlah subjek pada penelitian ini adalah 84 anak terdiri dari kelompok kasus 42 anak dan kelompok kontrol 42 anak. Variabel yang dianalisis meliputi karakteristik keluarga (pendidikan orangtua, pekerjaan orangtua, dan besar keluarga), karakteristik subjek (jenis kelamin, antropometeri saat lahir, status gizi saat lahir) status kesehatan, dan lingkungan pengasuhan, dan perkembangan kognitif anak. Hasil analisis menunjukkan bahwa pertambahan tinggi badan anak 0-4 tahun berpengaruh terhadap perkembangan kognitif anak prasekolah. Anak dengan pertambahan tinggi yang tidak sesuai dengan standar WHO berisiko 4,1 kali mengalami perkembanan kognitif yang terlambat. Sebagai upaya untuk meningkatkan pertumbuhan dan perkembangan kogntiif anak maka akses terhadap pendidikan dan pemberian lingkungan pengasuhan yang baik harus ditingkatkan. Pemenuhan kebutuhan gizi anak prasekolah yang sesuai agar pertumbuhan tinggi badan anak optimal dan dengan pemberian pola asuh psikososial yang baik dapat mengoptimalkan perkembangan kognitifnya. Selain itu, pemberian stimulasi yang sesuai dengan usia anak diperlukan untuk mendukung pertumbuhan dan perkembangan anak yang lebih optimal. [Penel Gizi Makan 2021, 44(2):105-113]